Comparing results of online GNSS services: A case study from Turkey - Gunes, Ozge; Demir, Deniz Oz (TAYLOR & FRANCIS LTD, 2022)
The goal of this paper is to compare academic and online GNSS processing services for CORS-TR. To determine whether differences in the coordinate components were statistically significant, statistical significance test and 3D coordinate transformation were applied. Furthermore, local coordinates analysed to show jumps that occurred to seismic events. While there are significant differences only in the Z coordinate component between GIPSY and GAPS in the Cartesian coordinate system, all differences in local coordinate components are insignificant. 3D coordinate transformation results included random errors and there are insignificant differences in terms of transformation parameters between GIPSY and online GNSS processing services.
Keywords: GNSS; Precise Point Positioning (PPP); Accuracy; Significance Test; Online PPP Services; 3D Transformation; GPS; Engineering; Geology; Remote Sensing